2021
DOI: 10.7150/ijms.50174
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaves extract ameliorates alcohol-induced liver damages through reduction of acetaldehyde toxicity and inhibition of apoptosis caused by oxidative stress signals

Abstract: Mulberry leaves (Morus alba L.), which are traditional Chinese herbs, exert several biological functions, such as antioxidant, anti-inflammation, antidiabetic, and antitumor. Alcohol intake increases inflammation and oxidative stress, and this increase causes liver injury and leads to liver steatosis, cirrhosis, and hepatocellular carcinoma, which are major health problems worldwide. Previous report indicated that mulberry leaf extract (MLE) exited hepatoprotection effects against chronic alcohol-induced liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…It has also been reported that mulberry leaves raise the peroxisome-proliferator-activated receptor-α; these leaves reduce chronic alcohol-induced liver oxidative stress; increase the expression of caveolin-1; and shut-down the epidermal growth factor receptor (EGFR), the signal transducer activator of transcription 3 (STAT3), and iNOS by diminishing alcohol-induced liver damage. Hence, it has been proposed that mulberry leaves can reverse the alcohol-induced liver injury [ 151 ].…”
Section: Ethanol and Antioxidantsmentioning
confidence: 99%
“…It has also been reported that mulberry leaves raise the peroxisome-proliferator-activated receptor-α; these leaves reduce chronic alcohol-induced liver oxidative stress; increase the expression of caveolin-1; and shut-down the epidermal growth factor receptor (EGFR), the signal transducer activator of transcription 3 (STAT3), and iNOS by diminishing alcohol-induced liver damage. Hence, it has been proposed that mulberry leaves can reverse the alcohol-induced liver injury [ 151 ].…”
Section: Ethanol and Antioxidantsmentioning
confidence: 99%
“…Mulberry leaves and grape-derived polyphenols have a wide range of biological activity (pleiotropic), as well as possible health-promoting effects [6,55], they have anti-inflammatory, anti-amyloidogenic, anti-cholinesterase, anti-amnesic, hypolipidemic, anti-aging agents and immunomodulatory and they are dietary supplements that can help delay the neurocognitive deterioration that occurs with age and Alzheimer's disease (AD) [56,57]. Mulberry leaves polyphenols reduced acetaldehyde toxicity and oxidative stress-induced apoptosis, suggesting that they could be used to treat alcohol-induced liver disease [58]. Several studies and clinical trials have established the importance of polyphenols in controlling numerous human illnesses, including SARS and MERS, which are related to COVID-19, by enhancing the host immune response to viral infections through multiple biological processes [20].…”
Section: Total Phenolics and Flavonoids Contentsmentioning
confidence: 99%
“…Many in vitro and in vivo studies confirmed that fruits such as the mango [ 144 ], grape [ 145 ], blueberry [ 110 ], mulberry [ 146 ], persimmon [ 147 ], pomegranate [ 148 ], cranberry [ 149 ], and wolfberry [ 150 ] play an important role against ALD. This ameliorative effect on ALD was mainly due to the presence of a tangible amount of bioactive compounds in fruits.…”
Section: Multicomponent Food Plant Extracts Against Aldmentioning
confidence: 99%
“…A previous study confirmed that mulberry possessed hepatoprotective effects in both animals and humans [ 157 ]. It was also reported that mulberry fruits and leaves could mitigate ALD via multiple pathways such as reducing lipid accumulation and lipid synthesis, decreasing OS, increasing fatty acid transport and fatty acid oxidation responses, and exerting an anti-inflammatory effect [ 146 , 158 ]. Gao et al [ 150 ] confirmed that wolfberry-derived zeaxanthin dipalmitate can protect the liver from alcohol-induced toxicity and concluded that daily intake of wolfberry may have a positive impact on ALD.…”
Section: Multicomponent Food Plant Extracts Against Aldmentioning
confidence: 99%